Justifications for using interactive online education - Yacoub Abu-Bajeh, Zaid; Alayham Abbas, Rabab (International Journal of Engineering and Technology, 2020)
The world is currently witnessing a renaissance of knowledge that can be described as the information era, the Educational environments became increasingly diverse, therefore, the institutions working in the educational field, are constantly seeking to create an efficient educational process to communicate knowledge to learners by the best possible ways and providing methods that aim to achieve the participation and create a link between the teacher and learners within the teacher guidance, in proportion to technological changes in the educational systems, where online education has undergone major changes in the organizational method of teaching. This prompts to focus on feedback as critically important in the educational process. The amount and type of interaction and feedback between the teacher and the learners depend on the link used; it is difficult to read "body language" of the learners over an audio link or recorded video, so the success of feedback process depends on face-to-face communication. This paper presents models of online education, and provides justifications for using interactive online education, and explains that there is a need for more researches in this field and take an active role in evaluating, selecting, and integrating tools and services that emphasize more teaching interactions.Â Â